2022
DOI: 10.1155/2022/4822337
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Prediction Using the Clinical Data and Ultrasomics-Based Model in Acute Respiratory Distress Syndrome (ARDS) Combined with Acute Kidney Injury (AKI)

Abstract: Objective. A model was constructed based on clinical and ultrasomics features to predict the prognosis of patients in the respiratory intensive unit (RICU) who had acute respiratory distress syndrome (ARDS) combined with acute kidney injury (AKI). AKI ensues after ARDS in RICU ordinarily. The prognostic prediction tool was further developed on this basis. Methods. We collected clinical and ultrasonic data from 145 patients who had ARDS combined with AKI and received continuous renal replacement therapy (CRRT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Similar to the previous studies, our results indicate that age [14], respiratory rate [15], Scr[16], INR [17,18] and complicated with CBD [19] or LD [20] are independent risk factors for critically ill patients. Moreover, our model showed that lactate was another independent risk factor, and higher lactate predicted worse prognosis of ARDS combined with AKI patients.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the previous studies, our results indicate that age [14], respiratory rate [15], Scr[16], INR [17,18] and complicated with CBD [19] or LD [20] are independent risk factors for critically ill patients. Moreover, our model showed that lactate was another independent risk factor, and higher lactate predicted worse prognosis of ARDS combined with AKI patients.…”
Section: Discussionsupporting
confidence: 90%